Modification of Electrode Surfaces for the Sensing of Toxic Gases - Hussain, Ghulam (Curtin University, 2017)
The work in this thesis aims to improve the sensitivity of amperometric sensors towards gases such as ammonia, hydrogen chloride, hydrogen, and oxygen in room temperature ionic liquids (RTILs). To achieve this, electrode surfaces are modified with 2D and 3D nanostructures, and different voltammetric techniques are applied. The results show what surface and which technique can be employed together with RTILs to produce low-cost, miniaturized, fast responding amperometric gas sensors.